2022
DOI: 10.1136/bmjgh-2021-007312
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the effects of COVID-19 on HIV treatment and care in Lusaka, Zambia: a before–after cohort study using mixed effects regression

Abstract: IntroductionThe Zambian Ministry of Health (MoH) issued COVID-19 mitigation guidance for HIV care immediately after the first COVID-19 case was confirmed in Zambia on 18 March 2020. The Centre for Infectious Disease Research in Zambia implemented MoH guidance by: 1) extending antiretroviral therapy (ART) refill duration to 6 multi-month dispensation (6MMD) and 2) task-shifting communication and mobilisation of those in HIV care to collect their next ART refill early. We assessed the impact of COVID-19 mitigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Thus, it is obvious that a shortage of ART medications is of great danger for PLHIV in terms of physical, psychological, and social wellbeing. To address this issue many countries and HIV services worldwide took measures such as sending medications via mail delivery, extended ART stock refills [ 61 ], incorporating telemedicine for healthcare provision continuation and decreasing the risk of exposure [ 62 ], broadening access to ART multi-month dispensing (MMD) policy, concentrating on community-based case-finding, and immediate, initiating ART among newly-diagnosed cases [ 63 ], launching telephone consultations, expanding ART refill sites [ 60 ], and HIV-positive patients task-shifting for early ART refill collection [ 64 ]. Hopefully, these measures assisted HIV services substantially to mitigate COVID-19-related ART disruptions and eventually caused an early return to normal ART adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is obvious that a shortage of ART medications is of great danger for PLHIV in terms of physical, psychological, and social wellbeing. To address this issue many countries and HIV services worldwide took measures such as sending medications via mail delivery, extended ART stock refills [ 61 ], incorporating telemedicine for healthcare provision continuation and decreasing the risk of exposure [ 62 ], broadening access to ART multi-month dispensing (MMD) policy, concentrating on community-based case-finding, and immediate, initiating ART among newly-diagnosed cases [ 63 ], launching telephone consultations, expanding ART refill sites [ 60 ], and HIV-positive patients task-shifting for early ART refill collection [ 64 ]. Hopefully, these measures assisted HIV services substantially to mitigate COVID-19-related ART disruptions and eventually caused an early return to normal ART adherence.…”
Section: Discussionmentioning
confidence: 99%
“…However, we are also aware that the major event that happened on a large scale during the period data was collected, soon after the U=U campaign initiative was launched in Zambia, was the COVID-19 pandemic. The effects of the COVID-19 pandemic on HIV care are well documented ( 22 24 ) and we think more will continue to be documented. In our study, therefore, the increased likelihood of having a detectable viral load among adult PLWHIV who were initiated on ART during the pandemic period was most likely due to HIV program services-related disruptions brought about by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, the World Health Organization and PEPFAR have recently recommended modifications to HIV service delivery in line with those employed in Kenya, including decentralized services, extended refills, and innovative recruitment and retention approaches to enable PrEP delivery despite pandemic‐related disruptions [ 20 , 21 , 22 ]. Limited data are available on the impact of such approaches, but two studies of modified ART delivery for persons living with HIV in Africa and Asia found that extending ART refill duration, task‐shifting, phone check‐ins with staff and community‐based ART delivery significantly increased retention and were acceptable for patients and staff [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%